2007
DOI: 10.1111/j.1813-6982.2007.00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Income Inequality, Reciprocity and Public Good Provision: An Experimental Analysis

Abstract: This paper analyses the impact of income inequality on public good provision in an experimental setting. A sample of secondary school students were recruited to participate in a simple linear public goods game where income heterogeneity was introduced by providing participants with unequal token endowments. The results show that endowment heterogeneity does not have any significant impact on contributions to the public good, and that consistent with models of reciprocity, low and high endowment players contrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 24 publications
4
36
0
1
Order By: Relevance
“…Kocher et al (2008) also tested for an effect of stake size on behavior and concluded that it had no significant effect on contribution levels (ibid.). Another study with urban high-school students lent further support to the above result, showing contributions to the public good averaging 33% throughout the game (Hofmeyr, Burns, and Visser 2007).…”
Section: Introductionmentioning
confidence: 58%
“…Kocher et al (2008) also tested for an effect of stake size on behavior and concluded that it had no significant effect on contribution levels (ibid.). Another study with urban high-school students lent further support to the above result, showing contributions to the public good averaging 33% throughout the game (Hofmeyr, Burns, and Visser 2007).…”
Section: Introductionmentioning
confidence: 58%
“…The first two hypotheses are based on the respective results by Hofmeyer et al (2007), whose experiment is very similar to ours.…”
Section: Hypothesis 2: All Player Types Contribute the Same Proportiomentioning
confidence: 95%
“…Investigating endowment heterogeneity in a linear VCM game, Hofmeyer et al (2007) find that endowment heterogeneity does not have any significant impact on the group-contribution level.…”
Section: Related Literaturementioning
confidence: 99%
“…Abstract: In a public-good experiment with heterogeneous endowments, we investigate if and how the contribution level as well as the previously observed fair-share rule of equal contributions relative to one's endowment (Hofmeyr et al, 2007; may be influenced by minimum-contribution requirements. We consider three different schedules: FixMin, requiring the same absolute contributions, RelMin, requiring the same relative contributions, and ProgMin, requiring minimum contributions that progressively increase with the endowment.…”
Section: Standard-nutzungsbedingungenmentioning
confidence: 99%
“…The first measure goes back to the fair-share rule in Hofmeyr et al (2007) and ; it measures the absolute contributions of the player types 11 For Type 10 (player 1) and Type 20 (player 4) the averages are based on ten players for each average, each. For Type 15 (players 2 and 3), the averages are based on twenty players.…”
Section: Comparison Within Treatmentsmentioning
confidence: 99%